2015
DOI: 10.1080/00222895.2014.953442
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Automated, Quantitative Test of Upper Limb Function

Abstract: The Rehabilitation Joystick for Computerized Exercise (ReJoyce, Rehabtronics Inc., Edmonton, Alberta, Canada), is a workstation on which participants exercise dexterous movement tasks in the guise of computer games. The system incorporates the ReJoyce Arm and Hand Function Test (RAHFT). Here the authors evaluate the RAHFT against the Action Research Arm Test (ARAT) and the Fugl-Meyer Assessment (FMA). All 3 tests were performed in 36 separate sessions in 13 tetraplegic individuals. Concurrent and criterion val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
0
30
0
3
Order By: Relevance
“…It takes about 4 minutes to perform. In a recent study on tetraplegic people, concurrent validity of the RAHFT was demonstrated by virtue of a high degree of correlation with ARAT scores [21] . The RAHFT thus offers a standardized, quantitative outcome evaluation of UL function, comparable to accepted and widely used qualitative tests.…”
Section: The Rejoyce Arm and Hand Function Test (Rahft) This Is An Amentioning
confidence: 99%
See 1 more Smart Citation
“…It takes about 4 minutes to perform. In a recent study on tetraplegic people, concurrent validity of the RAHFT was demonstrated by virtue of a high degree of correlation with ARAT scores [21] . The RAHFT thus offers a standardized, quantitative outcome evaluation of UL function, comparable to accepted and widely used qualitative tests.…”
Section: The Rejoyce Arm and Hand Function Test (Rahft) This Is An Amentioning
confidence: 99%
“…The Action Research Arm Test (ARAT) [17][18][19]. This clinical test has been shown to have construct validity for ADLs in stroke survivors [20] and is correlated with other UL function tests commonly used in clinical assessments [18,21,22]. …”
Section: Functional Electrical Stimulationmentioning
confidence: 99%
“…In this context, it is therefore also desirable that the assessment tool is capable of discriminating between individuals at a level of resolution commensurate with the delivery of personalized treatment plans. In this Special Issue, Prochazka and Kowalczewski (2015) describe the ReJoyce quantitative test of upper limb function, a measurement system that has been developed with the aim of addressing these requirements.…”
mentioning
confidence: 99%
“…En los estudios que proponen la automatización de la EFM (Hou et al, 2012;Olesh et al, 2014;Otten et al, 2015;Prochazka et al, 2015;Wang et al, 2014;Yu et al, 2016), con el fin de valorar la función motora de la ES, usualmente se aplican metodologías de entrenamiento de sistemas automáticos como los modelos de regresión. En los trabajos propuestos por (Olesh et al, 2014;Otten et al, 2015) se realiza análisis cinemático previo al uso de sistemas automáticos.…”
Section: Estado Del Arteunclassified
“…La demanda de nuevas técnicas de evaluación de la ES automatizadas surge debido al creciente número de pacientes con DCA, a los tratamientos avanzados tras el ictus, a la cantidad de tiempo de administración de la EFM y al tiempo limitado que los médicos pueden dedicar en las intervenciones de cada paciente (Hou et al, 2012;Olesh et al 2014;Otten et al, 2015;Prochazka et al, 2015;Wang et al, 2014;Yu et al, 2016).…”
Section: Estado Del Arteunclassified